Istihalah and Its Impacts on Food According to the Islamic Perspective - Al-Shiha, Ahmed Abdel Aziz; Kashim, Mohd Izhar Ariff bin Mohd; Mohamad, Mohd Nasran; Hasim, Nur Asmadayana (Journal of Ecohumanism, 2024)
Issues related to istihalah (transformation) are not only limited to matters of food and drink, but they are also concerned with the purity rulings of a human-need product in Islam. Nevertheless, this matter becomes more prevalent today when science and technology move forward swiftly with the latest diverse products. It has dramatically shifted the original form of food production through modern biotechnology methods, mixing ingredients from animal sources in food until it alters its original properties to new physical features such as cake, cultured meat, and genetically modified food. Following the realisation of the extensive mixing of halal and haram ingredients, the contemporary fatwa is being discussed among scholars in the food and beverage industry. Therefore, this research aimed to examine the process of istihalah that takes place, which can be categorised as istihalah tammah (perfect transformation) or istihalah naqisah (incomplete transformation), as well as explore the impacts on food that has gone through the process of istihalah. Next, the study also intended to examine the rulings of food that change in terms of properties, taste, smell, colour, physicality, and chemistry. The statements of fiqh scholars have been quoted and studied to address this concern. The analysis used a qualitative method by collecting sources from the Quran and Sunnah and the ijtihad of scholars obtained from reading such books as fiqh, food science, and websites. Ultimately, the study data substantiated that the process of istihalah is permissible in Islam if it is istihalah tammah and totally met. Nonetheless, deciding the halal status of a food product that has gone through istihalah is tricky because the PCR process in the laboratory needs to be done to confirm that the study results are authentic.